ANALISIS TANDA DALAM FILM THE BLACK PANTHER KARYA RYAN COOGLER - ANASTHASYA, ANNISA; RAMBING, ROSALINA R.; RATTU, JULTJE A.J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research entitles ?Analisis Tanda dalam Film The Black Panther Karya Ryan Coogler?. The aims of this research are to identify and classify the types of signs as well as to analyze the meaning of signs used in The Black Panther film. The writer uses the theory of Charles Sanders Pierce in the process of identifying, classifying, and analyzing each scene containing the signs used the representament aspect. The method used in this study is a descriptive method. To finish this study, the writer read some concepts related to the title about sign analysis and also downloaded resources from the internet. In collecting the data, the writer has watched 15 times The Black Panther film which is the object of the research. In addition to watching, the writer took pieces of images or visuals (screenshoot) from film scenes that are needed for research. The result of this research shows that based on the theory of Pierce there are three types of signs, namely icons, indexes, and symbols. There are 6 icon, 10 index, and 11 symbol. They were found from 22 scenes in The Black Panther film and each sign has different meanings. Keywords: Sign, Black Panther Film, Descriptive Methods